Under siege : my family's fight to save our nation - Trump, Eric, 1984- (Threshhold Editions, 2025)
"In this eye-opening memoir, Eric Trump relays surprising and gripping moments throughout his life and career as part of America's most powerful family. From his earliest memories of growing up as part of the Trump family to pivotal roles in the 2016 and 2024 presidential elections, spearheading strategies to combat lawfare, and leading the Trump Organization, Eric has been deeply invested in all aspects of his family's legacy. As one of his father's original apprentices, Eric has always strived to build on that foundation. As the Executive Vice President of the Trump Organization since 2015, Eric hasnavigated the dual worlds of politics and business, growing the company, while battling unprecedented opposition from the media, Democrats, and ongoing legal challenges. From raids on his childhood home,Mar-a-Lago, to near assassination attempts, from Russiagate to coldand corrupt court rooms, the fake news media, censorship, and character smears -- this wasn't just an attack on a president, or even his family. America itself was under siege. In this book, Eric offers an unfiltered look at the highs and lows of life in the Trump world ; how he took the reins of a multibillion-dollar empire at thirty-three years old ; enlightening stories from real estate to the boardroom of The Celebrity Apprentice, and the chaos of the campaign trail."--